Recording, documentation, and information management for the conservation of heritage places. - Letellier, Robin; Schmid, Werner; LeBlanc, Franȯis, 1946-; Eppich, Rand; Cabbi, Amel; Getty Conservation Institute. (London : Routledge, 2013)
Includes bibliographical references and indexes.